Xanthine oxidase inhibitory activity of isoflavonoids from Apios americana. (December 2019) - Kim, Jang Hoon; Jin, Chang Hyun
Graphical abstract: Highlights: Three isoflavonoids (1–3 ) were isolated by using column chromatography from Apios americana . They inhibited xanthine oxidase with IC50 values within 40 μg/mL. Binding parameters of enzyme with inhibitor were calculated by quenching study Molecular docking visualized their complex. Abstract: Xanthine oxidase (XO) is a form of xanthine oxidoreductase, a type of enzyme that plays a key role in the induction of hyperuricemia and raising superoxide radical level in blood. The present study was performed to evaluate the inhibitory activity of isoflavonoids (1 -3 ) isolated from the ethyl acetate fraction of Apios americana, on the catalytic reaction mediated by XO. The isoflavonoids exhibited potential inhibitory activity within microgram/mL along with quenching effect towards XO. A reduction in the respective IC50 values was observed in the presence of high concentration of substrate. Molecular docking study revealed Ser876 and Arg880 as the key amino acids involved in the interaction of the enzyme with inhibitor. Apparently, the results demonstrated isoflavonoids as one of the natural products with a potential inhibitory effect on XO.